PENGARUH PENAMBAHAN KITOSANSEBAGAI PENGAWET ALAMI PADA PEMBUATANSIRUP BUAH NAGA (Hylocereus polyrhizus) - Haryadi '; Evy Rossi; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research to get the best quality of dragon fruit syrup while storage with in the addition of chitosan. The research was conducted by Completely Randomized Design (CRD), that use 5 chitosan addition variable (0%; 0,5%; 1,0%; 1,5%; 2,0%) and than it repeated three times. Parameters measured were pH, fungi growth, sucrose concentration, viscosity and organoleptic were will be measure parameters organoleptik characteristics that consist of color, aroma, flavor, and overall assessment. The observations were analyzed using statistic. If the F calculated is greater or equal to F table will be conducted by 5% Duncan test. The addition of chitosan will decreased pH, sucrose concentration, viscosity and organoleptic. For the growth of the fungi was increased though addition of chitosan that extend the shelf life of dragon fruit syrup. The higher chitosan concentration will deareased level of preference from panelists. The optimum concentration chitosan addition was representative 0,5% chitosan addition. Keywords:Syrup,dragon fruit, chitosan